1998
DOI: 10.1111/j.1747-5457.1998.tb00781.x
|View full text |Cite
|
Sign up to set email alerts
|

Reflectance Retardation (Suppression) and Source Rock Properties Related to Hydrogen‐enriched Vitrinite in Middle Jurassic Coals, Danish North Sea

Abstract: Middle Jurassic high volatile bituminous A coals from the Danish North Sea may yield vitrinite reflectance values retarded by 0.10–0.14 %Rr The coals are low in liptinite content, and the reflectance retardation is related to the vitrinite composition. Vitrain (assumed to be pure vitrinite) was hand‐picked from eight samples and characterised by means of element analysis, Fourier Transform infrared spectroscopy and Rock‐Eval pyrolysis. In contrast to the vitrinite from samples yielding “true” reflectance value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(15 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…demonstrated in a study of confined pyrolysis on coal that the maturation of the residual solid kerogen was substantially accelerated due to the removal of hydrocarbons from the reaction system, confirming that hydrocarbons significantly retard the maturation of the residual solid kerogen. Furthermore, the results of the present study and by are consistent to the phenomenon of retardation of vitrinite reflectance which was documented by numerous previous studies (e.g., Hutton and Cook, 1980;Newman and Newman, 1982;Price and Barker, 1985;Raymond and Murchison, 1991;Petersen and Rosenberg, 1998).…”
Section: The Interaction Of Oil and Coal During Confined Pyrolysissupporting
confidence: 79%
See 1 more Smart Citation
“…demonstrated in a study of confined pyrolysis on coal that the maturation of the residual solid kerogen was substantially accelerated due to the removal of hydrocarbons from the reaction system, confirming that hydrocarbons significantly retard the maturation of the residual solid kerogen. Furthermore, the results of the present study and by are consistent to the phenomenon of retardation of vitrinite reflectance which was documented by numerous previous studies (e.g., Hutton and Cook, 1980;Newman and Newman, 1982;Price and Barker, 1985;Raymond and Murchison, 1991;Petersen and Rosenberg, 1998).…”
Section: The Interaction Of Oil and Coal During Confined Pyrolysissupporting
confidence: 79%
“…Suppression of reflectance of vitrinite has been widely documented (e.g., Hutton and Cook, 1980;Newman and Newman, 1982;Price and Barker, 1985;Raymond and Murchison, 1991;Petersen and Rosenberg, 1998). It has been suggested that the reflectance suppression is principally due to absorption by vitrinite clasts of aliphatic-rich fluids, emanating from different exinitic macerals, at different stages during coalification (e.g., Raymond and Murchison, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Diessel (1992) has likewise shown that coals formed during marine transgressions plot towards or above the upper limit of the bright coal band in the Seylers chart. The elemental data in the present study are derived from bulk humic coals, but Petersen and Rosenberg (1998) studied handpicked vitrinite concentrates. The concentrates of per-hydrous vitrinite from thermally mature petroleumgenerating Middle Jurassic coals in the Danish North Sea plotted close to or above the bright coal band and showed an average increase of ∼22% in HI compared to the concentrates of 'normal' vitrinite.…”
Section: Resultsmentioning
confidence: 99%
“…However, the increasing recognition of the ability of humic coal and Type III kerogen source rocks to generate and expel liquid petroleum has stimulated research, which has provided considerable new insights into the petroleum generative potential and generation and expulsion characteristics of these source rocks (for a thorough review, see Wilkins and George, 2002). Several studies have demonstrated that the depositional conditions influence not only the overall organic composition of coals, but also the chemical composition of the huminite/vitrinite, for example, by enhancing the hydrogen content in humic organic matter deposited in marine-influenced mires (Diessel, 1992;George et al, 1994;Petersen and Rosenberg, 1998;Petersen et al, 1996Petersen et al, , 1998aSykes, 2001).…”
mentioning
confidence: 96%
“…The type of the organic matter, the environment in which the organic matter forms (consisting of inorganic geochemical environment), and major and minor elements may catalyze and/or retard the OM evolution. Many papers have been published on the types of organic matter that retard maturation (Hunton and Cook, 1980;Zhao and Wang, 1990;Goodarzi et al, 1994;Petersen and Rosenberg, 1998).…”
Section: Function Of Pressurementioning
confidence: 99%